2014
DOI: 10.1371/journal.pone.0110752
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cardiomyocytes Derived from Isl1 Cardiac Progenitors via Bmp4 Stimulation

Abstract: As heart failure due to myocardial infarction remains a leading cause of morbidity worldwide, cell-based cardiac regenerative therapy using cardiac progenitor cells (CPCs) could provide a potential treatment for the repair of injured myocardium. As adult CPCs may have limitations regarding tissue accessibility and proliferative ability, CPCs derived from embryonic stem cells (ESCs) could serve as an unlimited source of cells with high proliferative ability. As one of the CPCs that can be derived from embryonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
1
16
0
4
Order By: Relevance
“…Also unexpectedly, Isl1 that has been regarded as specific for the SHF was detected in most cDNA preparations in the EHF stage regardless of Tbx5 expression, although fewer Tbx5 + CPs in the EB stage expressed Isl1 compared to Nkx2-5 + CPs ( Fig 2A ). This evidence supports previous reports that Isl1 is detected among the FHF population [ 44 47 ]. As indicated by previous studies, Isl1 expression was down-regulated in differentiated cardiomyocytes at E8.5 ( Fig 2A and 2B ) [ 10 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 93%
“…Also unexpectedly, Isl1 that has been regarded as specific for the SHF was detected in most cDNA preparations in the EHF stage regardless of Tbx5 expression, although fewer Tbx5 + CPs in the EB stage expressed Isl1 compared to Nkx2-5 + CPs ( Fig 2A ). This evidence supports previous reports that Isl1 is detected among the FHF population [ 44 47 ]. As indicated by previous studies, Isl1 expression was down-regulated in differentiated cardiomyocytes at E8.5 ( Fig 2A and 2B ) [ 10 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 93%
“…Following signalling activation via BMP type-1 or type-2 receptors, phosphorylated receptor-regulated SMADs form heterodimeric complexes with the common mediator SMAD4 and translocate to the nucleus to regulate gene expression. In the heart, BMP pathways play a pivotal role in the embryogenesis of the left ventricular chamber 33 , the differentiation of cardiac progenitor cells into functional cardiomyocytes 34 , maintenance of the balance between left ventricular growth and apoptosis 35 , initiation of fibrosis 35 , and Ca 2+ channel remodelling 36 . In analogy with the cardiac findings, previous studies demonstrated that BMP and TGF-β2 signalling pathways are also active in the eye 26 , 37 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo activation of β-catenin has been shown to promote the expansion of Isl-1 + CSCs through the regulation of fibroblast growth factor (FGF) signaling, suggesting that the Wnt/beta-catenin signaling pathway regulates renewal of Isl-1 + progenitors (Cohen et al, 2007;Qyang et al, 2007). Functional cardiomyocytes can be differentiated from Isl-1 + CSC population through bone morphogenic protein 4 (BMP4) signal activation (Cagavi et al, 2014). Another study showed that Notch1 signaling also regulates self-renewal, maintenance of cardiac progenitors, and the requirement for Notch1 activity in cardiac differentiation (Kwon et al, 2009).…”
Section: Isl-1 + Cellsmentioning
confidence: 99%